Recommendations on incurred sample stability (ISS) by GCC. (September 2014) - Lowes, Steve; LeLacheur, Richard; Shoup, Ronald; Garofolo, Fabio; Dumont, Isabelle; Martinez, Suzanne; Zimmer, Jennifer; Caturla, Maria Cruz; Couerbe, Philippe; Awaiye, Kayode; Fatmi, Saadya; Farmen, Raymond; et al.
The topic of incurred sample stability (ISS) has generated considerable discussion within the bioanalytical community in recent years. The subject was an integral part of the seventh annual Workshop on Recent Issues in Bioanalysis (WRIB) held in Long Beach, CA, USA, in April 2013, and at the Global CRO Council for Bioanalysis (GCC) meeting preceding it. Discussion at both events focused on the use of incurred samples for ISS purposes in light of results from a recent GCC survey completed by member companies. This paper reports the consensus resulting from these discussions and serves as a useful reference for depicting ISS issues and concerns, summarizing the GCC survey results and providing helpful recommendations on ISS in the context of bioanalytical method development and application.